Refractory craniofacial pain: is there a role of periodontal disease as a comorbidity? Dor refratária crânio-facial: há algum papel para a doença periodontal como morbidade associada? - Gisele Maria Campos Fabri; Silvia R.D.T. Siqueira; Caio Simione; Cibele Nasri; Manoel Jacobsen Teixeira; José Tadeu Tesseroli Siqueira (Arquivos de Neuro-Psiquiatria)
OBJETIVE: To evaluate the influence of the periodontal disease (PD), a chronic infection, in patients with chronic craniofacial pain complaints. METHOD: Twenty patients with chronic craniofacial pain and PD (CFP group) and 20 patients with PD (PD group) were assessed before and after periodontal treatment (baseline, 30 and 180 days after treatment). The paramenters evaluated were: plaque index, bleeding index, clinical probe insertion, Visual Analogic Scale (VAS) for pain intensity and Numerical Rating Scale (NRS) and Verbal Rating Scale (VRS) for the "chief complaint". RESULTS: After 180 days PD was controlled in both groups (p<0.001); the VAS decreased in CFP group (p<0.001); "chief complaint" improved (p=0.005 and p=0.027, respectively in CFP and PD group). VRS showed improvement between the groups in 30 (p=0.004) and 180 days (p=0.001). CONCLUSION: These results suggest a possible influence of periodontal disease, as a comorbidity, in refractory craniofacial pain patients and in their pain levels. OBJETIVO: Avaliar a influência da doença periodontal (DP) em pacientes com queixas de dores crônicas crânio-faciais. MÉTODO: Vinte pacientes com dor crônica crânio-facial e DP (CFP group) e 20 pacientes com DP (PD group) foram avaliados antes e depois do tratamento periodontal (baseline, 30 e 180 dias). Avaliações: índice de placa, índice de sangramento gingival, inserção clínica de bolsa, Escala Visual Analógica (VAS) para a dor, Escalas Numérica (NRS) e Verbal (VRS) para as "queixas principais". RESULTADOS: Após 180 dias a DP foi controlada em ambos os grupos (p<0,001); a VAS reduziu no CFP group (p<0,001); a "queixa principal" melhorou (p=0,005 e p=0,027, respectivamente nos grupos CFP e PD). A VRS mostrou diferença entre os grupos em 30 (p=0,004) e 180 dias (p=0,001). CONCLUSÕES: Estes resultados sugerem a provável influência da doença periodontal, como morbidade associada, nos níveis de dor de pacientes com dores crônicas crânio-faciais.